2016
DOI: 10.1016/j.jclepro.2016.03.175
|View full text |Cite
|
Sign up to set email alerts
|

Cradle to farm gate life cycle assessment of strawberry production in the United States

Abstract: The goal of this study was to develop a cradle to farm gate life cycle inventory and assess the environmental impacts of strawberry production in four major strawberry producing states of the United States: California, Florida, North Carolina and Oregon, representing 99% of the United States strawberry production. Life cycle environmental impacts depend strongly on geographic location and production practices. Data for California and North Carolina strawberry production were collected in collaboration with agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 15 publications
4
28
0
1
Order By: Relevance
“…In addition, a small fraction of irrigation pumps relies on diesel fuel rather than electricity. Impacts associated with machinery were not considered in this analysis, but a previous study of strawberry production in California found they were relatively insignificant due to the long life and limited operation hours of the machinery [26]. The energy, GHG emissions, and costs associated with diesel fuel for irrigation are included in the 'Applied Water' category, rather than the 'Direct Fuel' category.…”
Section: Direct Fossil Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a small fraction of irrigation pumps relies on diesel fuel rather than electricity. Impacts associated with machinery were not considered in this analysis, but a previous study of strawberry production in California found they were relatively insignificant due to the long life and limited operation hours of the machinery [26]. The energy, GHG emissions, and costs associated with diesel fuel for irrigation are included in the 'Applied Water' category, rather than the 'Direct Fuel' category.…”
Section: Direct Fossil Fuelmentioning
confidence: 99%
“…However, the existing literature is mostly specific to Europe; the GHG footprints of lemons, celery, and avocados have never been determined for the United States. The GHG footprint of strawberries in the United States has been estimated by three studies, two of which are specific to California, but not to Ventura County [25][26][27]. The applied water demand of all four crops has been previously estimated for California as a whole but not at the county level [28].…”
Section: Introductionmentioning
confidence: 99%
“…First, the environmental impact of fresh fruits and vegetables can vary significantly with geography. One study found the carbon footprint of strawberries produced in North Carolina to be three times higher than that of those produced in California [37]. A principal reason for this discrepancy is California's optimal growing climate, which delivers higher yields relative to other production regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, temperature and photoperiod interaction would hugely impact the flowering response and day-neutrality of the day-neutral cultivars. They will flower when temperatures are between 4 to 29°C (Rowley et al, 2011;Tabatabaie and Murthy, 2016), thus having the potential to extend harvest period that opens the window for off-season production (Reitmeier and Nonnecke, 1991). Dayneutral cultivar Albion in the annual plasticulture system can produce around 1 kg/plant marketable yield during a 6-month harvest period (from mid-May to mid-October) with better fruit quality than other day-neutral cultivars (Ballington et al, 2008).…”
mentioning
confidence: 99%